SELECTION OF CONSTRUCTIVE SOLUTIONS OF CAR ELEMENTS WITH SMALL EMPTY WEIGHT - Boronenko, Y. P.; Filippova, I. O. (Science and Transport Progress, 2017)
Purpose. The work is aimed to identify the reasons for the significantly higher coefficient of the empty weight of 1520 mm gauge cars in comparison with the freight cars in North America and to give recommendations for reducing the empty weight of freight cars. Methodology. As a methodology, a comparative evaluation of the strength, durability and stability of the minimum weight bearing structure made of various materials using the "space 1520" standards is applied. Findings. The authors found that with the use of high-strength steels the product weight can be reduced by a factor of five in comparison with the beam of steel 09G2S. If there is a welded joint in the construction, the weight of the structure will increase approximately by 2 times when calculated according to the "Norms for calculating and designing railroad cars of the Ministry of Railways of Russia, gauge 1520 mm (non-self-propelled)". And during calculations according to State Standard 33211-2013 "Freight cars. Requirements for strength and dynamic qualities" the weight increases almost 5 times and does not depend on the type of steel. Originality. It is revealed that the main criterion determining the empty weight of modern cars is the fatigue strength of the welded joint. It is shown that State Standard 33211-2013 and "Recommendations of the International Welding Institute" designate low endurance limits for high-strength steels and it is impossible to achieve the weight reduction if one adheres these recommendations. Practical value. The direction of actions to find the ways reducing empty weight of cars was developed: conditions for strength of welded joints of cars made of high-strength materials have been experimentally refined; methods for increasing the endurance of welded joints were developed; other types of connections are assumed.